Inspired to inspire others: Bekelech Belachew's story - International Livestock Research Institute (International Livestock Research Institute, 2019)
This is the story of Bekelech Belachew, a woman farmer from the Southern Nations Nationalists and Peoples region of Ethiopia, talking about the benefits of her involvement in the Africa RISING in the Ethiopian highlands project. The film was prepared by the Africa RISING to celebrate the 2019 International Women’s Day. With financial support from the United States Agency for International Development (USAID), the project is creating opportunities for smallholder farm households to move out of hunger and poverty through sustainably intensified farming systems that improve food, nutrition, and income security—particularly for women and children—and conserve or enhance the natural resource base.